2000
DOI: 10.1083/jcb.148.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Transcriptase Activity in Mature Spermatozoa of Mouse

Abstract: We show here that a reverse transcriptase (RT) activity is present in murine epididymal spermatozoa. Sperm cells incubated with human poliovirus RNA can take up exogenous RNA molecules and internalize them in nuclei. Direct PCR amplification of DNA extracted from RNA-incubated spermatozoa indicate that poliovirus RNA is reverse-transcribed in cDNA fragments. PCR analysis of two-cell embryos shows that poliovirus RNA-challenged spermatozoa transfer retrotranscribed cDNA molecules into eggs during in vitro ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 28 publications
(36 reference statements)
1
74
0
2
Order By: Relevance
“…Although there are few direct examples, genetic evidence from yeast are consistent with cDNAs being an intermediate in recombination (Derr and Strathern 1993). More directly, RNA injected into mouse (Giordano et al 2000) has been shown to yield cDNA. If the cDNA interacted with complementary displaced single-strand flaps that arise during normal DNA replication, this would result in stabilized double-stranded flaps that would be resistant to cleavage by the Fen1 flap-processing enzyme and a stabilized inverted repeat in the lagging strand .…”
Section: Genome Research 21mentioning
confidence: 88%
“…Although there are few direct examples, genetic evidence from yeast are consistent with cDNAs being an intermediate in recombination (Derr and Strathern 1993). More directly, RNA injected into mouse (Giordano et al 2000) has been shown to yield cDNA. If the cDNA interacted with complementary displaced single-strand flaps that arise during normal DNA replication, this would result in stabilized double-stranded flaps that would be resistant to cleavage by the Fen1 flap-processing enzyme and a stabilized inverted repeat in the lagging strand .…”
Section: Genome Research 21mentioning
confidence: 88%
“…Murine spermatozoa are also endowed with a functional RT activity, able to retrotranscribe exogenous RNA molecules into cDNA copies that can then be delivered to embryos during fertilization (Giordano et al, 2000). A similar RT activity is present in mouse cleavage embryos (CP, IS, EM, RL and CS, submitted).…”
Section: Introductionmentioning
confidence: 97%
“…More recently, the realization that retrotransposons can reshape the genome and contribute to modulation of gene expression has led to reconsider that hypothesis. Growing evidence indicate that RTcoding genes are expressed at low levels, if at all, in differentiated nonpathological tissues; in contrast, high expression is distinctive of germ cells (Kiessling et al, 1989;Giordano et al, 2000), embryos (Poznanski and Calarco, 1991;Packer et al, 1993), embryonic tissues (Mwenda, 1993), and undifferentiated and transformed cells (Deragon et al, 1990;Martin, 1991;Martin and Branciforte, 1993), suggesting that levels of RT expression are linked to the proliferative potential of the cell. In addition, RT gene activity is upregulated by a variety of stimuli acting at the genome-wide level, for example, cellular stress (Hagan et al, 2003), heat shock, cycloheximide, adenovirus infection (Li and Schmid, 2001), genotoxic agents (Hagan and Rudin, 2002), and DNA base analogs (Khan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%